Assessing the Effect of Large Class Size and Pupils Academic Performance in Public Primary School in Rukungiri Municipality. - Kashumbusha, Robert (Kabale University, 2024)
The study was about examining the effect of large class sizes and pupils' academic Performance in public primary Schools in Rukungiri Municipality. The study was guided by three objectives which were: to find out the relationship between large class size and pupils' academic performance, to find out the effect of class size on pupils' academic performance in selected schools in Rukungiri Municipality, to identify the pupil's enrollment and number of teachers in public schools. A targeted population of 66 respondents was considered and these included Headteachers, teachers, and pupils. Both simple random and purposive sampling techniques were used in identifying the study sample size. The methods that were used in data collection included questionnaires, observation, and interviews. Data collected was edited, coded, entered into the computer, and analyzed with Excel, a Microsoft statistical package, the results were presented in tables. Based on results from the study, 100% of the respondents were aware of the relationship between large class size and pupils' academic performance, and these- included smaller classes encourage participation or interaction as students may receive more support from classmates, teachers in small classes are more I likely to give individual attention to students, effectively control and manage the classroom and build better relationships with students, class size may also influence teachers' interpersonal styles, small classes are more visible and more likely to engage in learning and social behaviors during class, class size has the potential to affect how students interact with each other. The study findings revealed the effect of class size on pupils' academic performance in selected schools in Rukungiri Municipality. These included quality teaching and assessment suffering in large, lack of funding was perceived to impinge well beyond the classroom to the workplace and ultimately to the state of the economy, lack of appropriate value associated with teaching, school administration creating an environment that affects academic standards either positively or negatively. Objective three, it was found out as indicated by the respondents from public primary schools in Rukungiri municipality that the pupil enrollment and number of teachers in public schools and the introduction of Universal Primary Education in Uganda, the skill that teachers exhibit in teaching influences the pupil enrollment, a teachers lack of experience may translate into low enrollment of students, repetition, and dropout, teachers' experience is important to students' learning